2004
DOI: 10.1111/j.0141-9854.2003.00578.x
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy, reproducibility and clinical utility of the CoaguChek S portable international normalized ratio monitor in an outpatient anticoagulation clinic

Abstract: The accuracy and reproducibility of the CoaguChek S, and its clinical agreement with conventional laboratory international normalized ratio (INR) determination, were evaluated in an outpatient anticoagulation clinic setting. Forty-three patients provided 248 paired INR measurements for analysis. The paired results were highly correlated (r = 0.90). The mean coefficient of variation for the CoaguChek S for a random sample of 21 patients with three repeated tests each, was 4%. Clinical applicability was also mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
20
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 26 publications
7
20
0
Order By: Relevance
“…These are comparable with agreements found in other studies. 15,[17][18][19] For the analysis of proportion of dual readings within 0.5 units, the results were again similar to those found in other studies, although for the higher INR range, the proportion of dual results >4.0 in remote areas the agreement was only 50% of the time compared to urban (68%) and rural (82%) patients. This was a lower percentage of agreement than found by Jackson et al (57%) for practices based in rural Australia 17 .…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…These are comparable with agreements found in other studies. 15,[17][18][19] For the analysis of proportion of dual readings within 0.5 units, the results were again similar to those found in other studies, although for the higher INR range, the proportion of dual results >4.0 in remote areas the agreement was only 50% of the time compared to urban (68%) and rural (82%) patients. This was a lower percentage of agreement than found by Jackson et al (57%) for practices based in rural Australia 17 .…”
Section: Discussionsupporting
confidence: 87%
“…In two Australian studies using CoaguChek S, the same device used in the Trial, agreement was found to be 90% against expanded criteria and 88% against narrow criteria in an outpatient clinic, and 93% against expanded criteria and 90% against narrow criteria in rural practice. 15,17 The Trial found 86% of dual measurements were within 0.5 INR units, which is similar to that found by Jackson et al 15 (83%), Jackson et al 17 (88%) and Douketis et al 19 (79%). The Trial's results on the percentage of dual measurements within 0.5 units achieved similar results for the lower result ranges, but the Trial achieved much higher measurements of agreement in the higher INR ranges than other studies.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations